2010
DOI: 10.1007/s00428-010-0945-1
|View full text |Cite
|
Sign up to set email alerts
|

Serrated polyps of the colon and rectum (hyperplastic polyps, sessile serrated adenomas, traditional serrated adenomas, and mixed polyps)—proposal for diagnostic criteria

Abstract: Until recently, two major types of colorectal epithelial polyps were distinguished: the adenoma and the hyperplastic polyp. While adenomas-because of their cytological atypia-were recognized as the precursor lesions for colorectal carcinoma, hyperplastic polyps were perceived as harmless lesions without any potential for malignant progression mainly because hyperplastic polyps are missing cytological atypia. Meanwhile, it is recognized that the lesions, formerly classified as hyperplastic, represent a heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
1
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 34 publications
(32 reference statements)
5
74
1
6
Order By: Relevance
“…They could also be missed more frequently, since they are mostly flat lesions and located in the right colon. Histological criteria have been developed on the basis of morphological changes and marker expressions [2,15]. The malignant potential of SSA has been regarded as substantial by some groups [23], but no consensus exists about both their occurrence and overall cancer risk in a broad community setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They could also be missed more frequently, since they are mostly flat lesions and located in the right colon. Histological criteria have been developed on the basis of morphological changes and marker expressions [2,15]. The malignant potential of SSA has been regarded as substantial by some groups [23], but no consensus exists about both their occurrence and overall cancer risk in a broad community setting.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 Microscopic criteria for diagnosis of SSA according to the German Society of Pathology [15] • Hyperserration, serration in the lower third of the crypts with and without branching of the crypts • T-or L-shaped crypts above the muscularis mucosae Secondary outcomes & There is a likelihood of a shortening of recommended follow-up intervals on a per-patient basis, namely, shortening from 10 years (based on a diagnosis of HP only) to either 3 or 5-10 years based on the presence of adenomas. For this analysis, SSA were treated like adenomas with respect to follow-up recommendations [16,17], although this practice might not be regarded as finally established.…”
Section: Case Selection and Reassessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of BRAF and KRAS mutations in serrated polyps negative for dysplasia and serrated polyps positive for low-grade dysplasia in our study closely resembles the rates reported in sporadic sessile serrated adenoma/polyps and traditional serrated adenomas, respectively. 4,5,26 This observation, in conjunction with their corresponding sex and anatomical site disparities, suggests that biologic parallels exist with sporadic sessile serrated adenoma/polyps and traditional serrated adenomas, despite the origin of at least 97% of our serrated polyps within chronically diseased inflammatory bowel disease mucosa. Although supervening cytologic dysplasia has been reported in up to 15% of sporadic sessile serrated adenoma/polyps, 27,28 we did not encounter this phenomenon in our study, where serrated polyps with cytologic dysplasia histologically resembled sporadic traditional serrated adenomas.…”
Section: Modern Pathology (2015) 28 1584-1593mentioning
confidence: 94%
“…1 However, the biological significance of these two morphological patterns is still unknown. Although some pathologists diagnose tumors with combined features as mixed hyperplastic/adenomatous polyps or mixed polyps with a description of the constituent components, 17,18 mixed polyps have also been reported to share similar molecular changes and implicate morphological progression to malignancy. 13,19 Jass et al 13 reported that traditional serrated adenoma with dysplastic epithelium resembling conventional adenoma displayed a high frequency of KRAS mutation, whereas Kim et al 7 linked this traditional serrated adenoma to a lower frequency of BRAF mutation.…”
mentioning
confidence: 99%